Women Entrepreneurship In Business Trends; Challenging Issue For Growth - PANDEY, DR TARKESHWER (IJRDO - Journal of Applied Management Science, 2015)
Studies have shown that successful Women entrepreneurs start their businesses as a second or third profession. Because of their previous careers, women entrepreneurs enter the business world later on in life, around 40–60 years old. As women are now overtaking their male peers when it comes to education, having higher education degrees is one of significant characteristics that many successful female entrepreneurs have in common.